Prevalence and PCR detection of Salmonella spp. and Escherichia coli in water used during live transportation of climbing perch (Anabas testudineus) in Bangladesh - Hossain, Md. Mubarack; Bhuiyan, A. N. M. Rezvi Kaysar; Uddin, Md. Naim; Haider, Md Nurul (Journal of King Abdulaziz University: Marine Sciences, 2024)
This research investigated the incidence of two foodborne pathogens, Salmonella spp. and Escherichia coli in water used during live transportation of climbing perch (Anabas testudineus). Assessments were conducted in three commercially important fish supply channels of Bangladesh, starting from an important production area, Muktagacha, Mymensingh to Dhaka (supply channel 1), Sylhet (supply channel 2), and Rajshahi (supply channel 3). Water samples were collected from 0 hours (at the time of loading) to reaching at the final destination (unloading points/ retail markets) at every 2 hours interval during transportation. To assess the prevalence of Salmonella spp. and E. coli, Salmonella-Shigella (SS) agar and Eosin methylene blue (EMB) agar plate counts were taken into consideration. For confirmation and PCR detection, a total of 52 isolates were obtained from those cultured plates based on the colony characteristics. The finding showed a gradual increase in SS- and EMB agar plate counts in all the supply channels. Out of the 52 isolates, 10 (19%) were detected as positive for Salmonella spp., while 38 (73%) as positive for E. coli. It was assessed that the pond waters of the cultured areas might be the primary sources of contamination of these two foodborne pathogens.